2011
DOI: 10.1371/journal.pone.0024426
|View full text |Cite
|
Sign up to set email alerts
|

Eph/Ephrin Profiling in Human Breast Cancer Reveals Significant Associations between Expression Level and Clinical Outcome

Abstract: Pre-clinical studies provide compelling evidence that Eph family receptor tyrosine kinases (RTKs) and ligands promote cancer growth, neovascularization, invasion, and metastasis. Tumor suppressive roles have also been reported for the receptors, however, creating a potential barrier for clinical application. Determining how these observations relate to clinical outcome is a crucial step for translating the biological and mechanistic data into new molecularly targeted therapies. We investigated eph and ephrin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
109
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 41 publications
6
109
2
2
Order By: Relevance
“…68 Epigenetic repression of EphA5 was associated with predictors of poor prognoses including high tumor grade, lymph node metastasis, and progesterone receptor negative status indicative of resistance to endocrine therapy. 86 A genome-wide association study of more than 2,000 invasive breast cancer samples and matched controls revealed changes in EphB1, EphA3, and EphA7.…”
Section: Eph Receptor and Ephrin Signaling In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…68 Epigenetic repression of EphA5 was associated with predictors of poor prognoses including high tumor grade, lymph node metastasis, and progesterone receptor negative status indicative of resistance to endocrine therapy. 86 A genome-wide association study of more than 2,000 invasive breast cancer samples and matched controls revealed changes in EphB1, EphA3, and EphA7.…”
Section: Eph Receptor and Ephrin Signaling In Breast Cancermentioning
confidence: 99%
“…For example, increased EphA2 expression has been found in aggressive breast cancers and was significantly correlated with decreased overall survival and invasive ductal carcinoma. 68 Although breast ductal carcinomas express EphA2 and ephrin-A1, ligand expression is reduced in corresponding lymph node metastases. Breast carcinoma cell line invasiveness also correlated with a loss of ephrin-A1 and mislocalization of EphA2 in the cytoplasm.…”
Section: Eph Receptor and Ephrin Signaling In Breast Cancermentioning
confidence: 99%
“…Preclinical models provide compelling evidence that EPHA2 overexpression increases breast tumor formation, malignant progression, and therapeutic resistance to antitumor therapies (9,13). Large-scale expression profiling for EPHA2 transcript levels in relation to clinical outcome revealed a negative association between EPHA2 transcript levels and overall survival in breast cancer (14). These findings are consistent with preclinical studies in genetically engineered mouse models of breast cancer, which revealed distinct roles for EPHA2 in the tumor epithelia, in which EPHA2 signaling drives tumor cell proliferation and survival, and in the tumor microenvironment, in which EPHA2 is required for tumor angiogenesis (9,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Eph receptor and ephrin expression is also disregulated during cancer progression, and in many cases knowing the expression levels of specific Eph receptors and ephrins could be useful for diagnostic and prognostic purposes. 2,[8][9][10] Profiling Eph receptor and ephrin expression in tumors may also be helpful in the future to design targeted and personalized therapies as well as to assess their effectiveness.…”
Section: Introductionmentioning
confidence: 99%